Time Complexity Analysis of Graph Algorithms in Big Data: Evaluating the Performance of PageRank and Shortest Path Algorithms for Large-Scale Networks - Kondaveeti, Dharmeesh; Inampudi, Rama Krishna; Kurkute, Mahadu Vinayak (Journal of Science & Technology, 2024)
This paper delves into the time complexity analysis of two prominent graph algorithms, PageRank and shortest path algorithms, with a focus on their performance in large-scale networks commonly encountered in big data systems. The need to process extensive network data efficiently has led to an increased emphasis on understanding the computational complexity of algorithms applied to graph-based structures, especially in scenarios where the size of the data becomes a critical factor in performance evaluation. As the volume of network data grows exponentially, algorithms designed for tasks such as ranking web pages or finding optimal paths between nodes must be assessed not only for their accuracy but also for their scalability and efficiency in terms of computational resources. PageRank, a foundational algorithm for ranking web pages, operates on the principle of recursively measuring the importance of nodes within a network based on their connectivity. The algorithm’s time complexity is dependent on both the number of nodes and edges in the graph, as well as the convergence criterion used. This paper evaluates the iterative nature of PageRank, examining its time complexity with respect to various parameters such as network size, convergence tolerance, and damping factor. Furthermore, the paper explores how different optimization techniques, including parallel and distributed computing, affect the performance of PageRank when applied to large-scale networks. Special attention is given to the algorithm’s behavior in both static and dynamic network environments, where the underlying graph structure may evolve over time. The paper aims to provide a comprehensive understanding of how PageRank’s computational complexity grows as the scale of the network increases, and how this growth can be mitigated through algorithmic and infrastructural optimizations. Similarly, shortest path algorithms, such as Dijkstra’s algorithm and the Bellman-Ford algorithm, are analyzed with respect to their time complexity in the context of large-scale graphs. These algorithms are crucial for applications that require determining the optimal path between nodes, a common requirement in network routing, transportation logistics, and social network analysis. The performance of these algorithms is evaluated based on different graph structures, such as sparse versus dense graphs, and under various constraints, such as edge weights and graph directionality. The paper discusses how the choice of algorithm impacts the overall time complexity, especially in cases where real-time computation is critical. It also examines the role of heuristics, like A*, in reducing the computational overhead for certain types of networks. To provide a holistic view, this paper integrates empirical analysis with theoretical evaluations, comparing the worst-case, best-case, and average-case time complexities of PageRank and shortest path algorithms. Through the use of experimental simulations, the paper showcases how these algorithms perform in practice when applied to datasets containing millions or billions of nodes and edges. The results of these simulations highlight the practical limitations of these algorithms when used in large-scale networks, and suggest possible improvements, including algorithmic enhancements and hardware-accelerated implementations. In addition to providing a detailed complexity analysis, the paper also addresses the trade-offs involved in the design and deployment of these algorithms in distributed computing environments. With the rise of big data platforms such as Hadoop and Apache Spark, the scalability of graph algorithms has become an increasingly important area of research. The paper examines how these distributed platforms handle the execution of PageRank and shortest path algorithms, focusing on the communication overhead, load balancing, and fault tolerance issues that arise when processing large-scale networks. The interplay between algorithmic complexity and distributed system architecture is discussed, highlighting the need for fine-tuning both the algorithm and the infrastructure to achieve optimal performance in big data contexts. Furthermore, the paper addresses the practical implications of these time complexity analyses in real-world applications. For instance, the application of PageRank in search engine optimization and social media influence measurement, and the use of shortest path algorithms in logistics, transportation, and telecommunication networks, underscore the importance of understanding the computational limitations and scalability challenges of these algorithms. The findings presented in this paper will be relevant not only to researchers in the field of graph theory and big data but also to practitioners who must choose appropriate algorithms for handling large-scale network data. Overall, this paper contributes to the field by providing a comprehensive analysis of the time complexity of PageRank and shortest path algorithms in the context of big data. By combining theoretical insights with empirical evaluations, the paper offers a robust framework for understanding the scalability challenges of these algorithms when applied to large-scale networks. Additionally, the paper identifies key areas for future research, including the development of more efficient algorithms for large-scale graph processing, the optimization of existing algorithms for distributed environments, and the exploration of new graph-theoretic approaches for handling the increasing complexity of big data networks.